Mango peels-assisted synthesis of carbon quantum dots for potential optical sensing of diazinon - Nor Asri, Nor Afiqah; Fen, Yap Wing; Muhamad Fauzi, Nurul Illya; Kamaruzzaman, Nur Aqilah; Mohamed Khaidir, Rahayu Emilia; Hashim, Hazwani Suhaila; Anuar, Muhammad Fahmi; Mohd Zailani, Muhammad Amir Zakwan; Mohd Fadzil, Ahmad Danish Iskandar; Mahamad Basari, Nur Nadia Amira; Kamarudin, Mazliana Ahmad; Abdullah, Huda (Nature Research, 2026)
Recently, carbon quantum dots (CQDs) have received widespread attention for their attractive properties and potential in sensing applications; however, their production often uses harmful materials and high energy. In this study, CQDs were acquired from mango peels using green hydrothermal method at 200 °C for 3, 6, 9, 12, and 15 h, using water as the solvent. The optical behavior of CQDs with different time synthesis, indicating photoluminescence (PL) emissions wavelength (441–447 nm), varying absorbance (0.80–0.99), and slight changes in optical bandgap (3.935–3.825 eV), showing synthesis time influences optical behavior. The CQDs with 3 h synthesis time were chosen to undergo structural characterization due to the most left shifted in PL emission, indicating the smallest particle size. Transmission electron microscopy analyzed that the CQDs were monodispersed with the average particle size was 3.54 nm, while energy dispersive X-ray results exhibited high carbon content of 97%. Fourier transform infrared analysis proves the formation of CQDs nanoparticles by the existence of hydroxyl, carbonyl, and carboxyl functional groups. Atomic force microscopy confirmed a root mean square roughness increased from 0.71 to 1.02 nm, indicating CQDs attachment, and the gold-CQDs thin film was later used as the surface plasmon resonance (SPR) sensing layer. The develop gold-CQDs thin film-based SPR sensor was successfully tested in diazinon concentration range from 0 to 100 nM, with a limit of detection as low as 0.01 nM and sensitivity of 0.0153º nM-1. These results indicate that the potential of mango peels-derived CQDs as sustainable nanomaterials for optical sensing applications, particularly in environmental monitoring using SPR-based technology.